INTENSITAS DAN LAJU INFEKSI PENYAKIT KARAT DAUN Uromyces phaseoli PADA TANAMAN KACANG MERAH - Manengkey, Guntur S.J.; Senewe, Emmy (Universitas Sam Ratulangi, 2011)
ABSTRACT Rust leaf on red bean is major desease in the area of Tonsewer, Toure dan Tumaratas village. The aim of the study was to determine the intensity and infection rate of rust disease on red bean at Tonsewer, Toure and Tumaratas village, The method used was survey by drawing a diagonal line at four points and one point in the center of each farm. Hence, there were five points that were used for sampling area for calculating the intensity and the infection rate caused by leaf rust Uromyces phaseoli. The result showed that red bean farm in the village of Tonsewer, Toure and Tumaratas had been infected by rust disease caused by the fungus Uromyces phaseoli . The average of attacking intensity was 62.29% in Tonsewer. Whereas, Toure and Tumaratas were 61.71% and 62.29 respectively. The average of infection rate was 0.239 per unit per day in the Tonsewe. While in the Toure and Tumaratas were 0.189 and 0.208 per unit per day respectively . Keyword : Intensity and infection rate,Red Bean